Corrigendum / Erratum / Retraction (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2018)
RETRACTION TO:Maulidyawati, D., Irham, M. (2018). Analisis Metakognisi Peserta Didik dalam Pemecahan Masalah pada Materi Turunan. Kreano, Jurnal Matematika Kreatif-Inovatif, 9(1), 84-92. DOI: 10.15294/kreano.v9i1.13125.This article has been retracted by Publisher based on the following reason:Requested by Author by Email at May 9th, 2018.Editor then checked by Google Scholar and found similar article published on PROCEEDINGS ELPSA CONFERENCE 2017 [Irham, M. (2018, March). Analisis Metakognisi Peserta Didik dalam Pemecahan Masalah Pada Materi Turunan. In PROCEEDINGS ELPSA CONFERENCE 2017 (Vol. 1, No. 1).]Author violates Kreano, Jurnal Matematika Kreatif-Inovatif’s Ethics Statement on Author’s rule number 3. (See https://journal.unnes.ac.id/nju/index.php/kreano/pages/view/Ethics-Statement). The Editor has difficult detecting this problem during submission process.